Benzothiazole-based heterodipodal chemosensor for Cu2+ and CN– ions in aqueous media. Issue 39 (26th September 2019) - Sik Na, Won; Raj, Pushap; Singh, Narinder; Jang, Doo Ok
Graphical abstract: Highlights: A benzothiazole-based heterodipodal chemosensor has been synthesized. Cu 2+ ions were detected in aqueous media using fluorescence spectroscopy. Limit of detection for Cu 2+ ions in aqueous media was in nanomolar range. The Cu 2+ complex of chemosensor recognized CN – anions in aqueous media. Abstract: A simple and selective chemosensor, A, was developed for recognizing Cu 2+ . The emission spectra of receptorA showed a fluorescence quenching response upon addition of Cu 2+ with a low detection limit of 4.51 nM, significantly less than the WHO recommended guideline for drinking water. In addition, the formedA∙ Cu 2+ complex was examined for secondary sensing of anions. TheA∙ Cu 2+ complex showed selectivity for CN – via a recovering emission profile ofA .